2008
DOI: 10.1159/000163091
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of 2n = 60 <i>Spalax leucodon</i> cytotypes (Spalacidae, Rodentia) in Turkey by means of classical and molecular cytogenetic techniques

Abstract: Comparative studies among seven populations of 2n = 60 S. leucodon employing classic cytogenetics (G- bands, C-bands, AgNOR-staining), fluorochrome staining, and fluorescence in situ hybridization of telomeric and rDNA probes are reported here for the first time. The studied specimens were assigned to two cytotypes: 2n = 60W and 2n = 60R. The basic karyotype of both cytotypes consisted of eight pairs of subtelocentric and 21 pairs of acrocentric autosomes, subtelocentric X and acrocentric Y chromosomes. Both c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 42 publications
(24 reference statements)
4
41
2
Order By: Relevance
“…Most chromosomal races are, however, differentiated without a barrier. Although chromosomal races are close together geographically in Turkey, hybridization does not occur (Nevo et al, 1994;Coşkun, 2003;Sözen, 2004;Matur and Sözen, 2005;Sözen et al, 2006aSözen et al, , 2006bKankılıç et al, 2007;Ivanitskaya et al, 2008). We neither recorded any hybrid specimens in the study area nor found polymorphism in G-and C-banding patterns.…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…Most chromosomal races are, however, differentiated without a barrier. Although chromosomal races are close together geographically in Turkey, hybridization does not occur (Nevo et al, 1994;Coşkun, 2003;Sözen, 2004;Matur and Sözen, 2005;Sözen et al, 2006aSözen et al, , 2006bKankılıç et al, 2007;Ivanitskaya et al, 2008). We neither recorded any hybrid specimens in the study area nor found polymorphism in G-and C-banding patterns.…”
Section: Discussionmentioning
confidence: 63%
“…Previous banding studies (Ivanitskaya et al, 1997(Ivanitskaya et al, , 2008) suggested a high level of chromosomal divergence, which means that it is possible to consider these chromosomal races as having well-differentiated chromosomal lineage within the xanthodon group. Our phylogenetic tree indicates that each group (west, north, middle, and Thrace) is well differentiated (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations